Sosialisasi Sekolah Siaga Bencana (SSB) Sebagai Upaya Meningkatkan Kesiapsiagaan Siswa di SMA Athira Makassar - Meliyana, Sitti Masyitah; Muthahharah, Isma; Mar'ah, Zakiyah; Hafid, Hardianti; Juhari, Agusalim (Program Studi Manajemen FEB UNM, 2026)
Indonesia is a disaster-prone country, making early preparedness efforts essential, particularly in the school environment. This community service activity aims to improve students’ knowledge and preparedness through the socialization of the Disaster Preparedness School (Sekolah Siaga Bencana/SSB) program at SMA Athira Makassar. The methods used include interactive lectures, discussions, and evacuation simulations, with evaluation conducted using pre-test and post-test. The results show an increase in the average preparedness score from 58.9 in the pre-test to 83.8 in the post-test, indicating an improvement of 24.9 points. The highest increase was found in the understanding of evacuation procedures. These findings indicate that the SSB socialization program is effective in enhancing students’ knowledge and disaster preparedness. Therefore, this activity contributes to fostering a disaster aware culture in schools and can serve as a model for implementing education-based disaster preparedness programs.